Characterization of the oxygen-tolerant formate dehydrogenase from Clostridium carboxidivorans - Brouwer, Eva-Maria; Medipally, Hitesh K. R.; Schwab, Saskia; Song, Shanshan; Nowaczyk, Marc M.; Hagemann, Martin (Frontiers in Microbiology, 2025)
Fixation of CO2 into the organic compound formate by formate dehydrogenases (FDHs) is regarded as the oldest autotrophic process on Earth. It has been proposed that an FDH-dependent CO2 fixation module could support CO2 assimilation even in photoautotrophic organisms. In the present study, we characterized FDH from Clostridium carboxidivorans (ccFDH) due to its ability to reduce CO2 under aerobic conditions. During the production of recombinant ccFDH, in which the selenocysteine codon was replaced by Cys, we were able to replace the W with Mo as the transition metal in the ccFDH metal cofactor, resulting in a two-fold increase of 6 μmol formate min−1 in enzyme activity. Then, we generated ccFDH variants in which the strict NADH preference of the enzyme was changed to NADPH, as this reducing agent is produced in high amounts during the photosynthetic light process. Finally, we showed that the native ccFDH can also directly use ferredoxin as a reducing agent, which is produced by the photosynthetic light reactions at photosystem I. These data collectively suggest that ccFDH and, particularly, its optimized variants can be regarded as suitable enzymes to couple formate production to photosynthesis in photoautotroph organisms, which could potentially support CO2 assimilation via the Calvin–Benson–Bassham (CBB) cycle and minimize CO2 losses due to photorespiration.